The financialisation of the fishing industry: Galicia as a case study - Federico Martin Palmero; Fernando González Laxe (European Journal of Government and Economics (EJGE), 2021)
Successive technical and organizational innovations have modelled the current structure and composition of the fishing industry. The market structure varies considerably between countries and the fish species they catch. There is a generalised global convergence towards an industrial-outsourced model, in which companies occupy a central and basic position in economic strategies. Two predominant key trends are identified: financialisation and the monopolisation of fishing areas. This paper begins with an analysis of the fishing sector from the perspective of the presence of investment funds that hold stakes in companies specialising in a principal region of Europe.
Keywords: 330; fisheries sector; financialisation; investment funds; business concentration